التحديد المسبق لحاجات المصلحة المتعاقدة وأثره على نجاعة الصفقة العمومية - ملاتي, معمر (University of Eloued جامعة الوادي, 2021)
يعتبر النجاح في عملية التحديد المسبق للحاجات المرتبطة بالطلب العمومي الملّبى عن طريق الصفقات العمومية، من أهم ضمانات الشراء الناجح والذي يعني نجاعة الطلب العمومي ورشادة في المال العام، هذه المرحلة التحضيرية لإبرام الصفقة العمومية، تضمنت ضوابطها المادة 27 من المرسوم الرئاسي 15/247، المتضمن الصفقات العمومية وتفويضات المرفق العام. هذا المقال تضمّن معالجة أهمية التحديد المسبق للحاجات في نطاق إبرام الصفقات العمومية وأثره على طرفي الصفقة العمومية، المصلحة المتعاقدة والمتعامل المتعاقد، من خلال قراءة قانونية للمادة المذكورة أعلاه، ومختلف النصوص ذات الصلة. What guarantees most a successful procurement, meaning the efficiency of the public submission and its guidance in public funds, is the success in the pre-determination of the needs associated with the public submission, fulfilled through public transactions. The regulations of this preparatory phase for concluding public transactions are included in Art. 27 of the Presidential Decree no. 15/247, bearing public transactions and public service delegations. This paper deals with the importance of pre-determining the needs within the scope of concluding public transactions, and its impact on the parties of the public contract, the contracting authority and the contracting dealer, through a legal reading of the aforementioned article and various related texts.
مجلد12، عدد1
Keywords: التحديد المسبق للحاجات_ مصلحة متعاقدة_ طلب عمومي_ صفقة عمومية_ تفويض المرفق العام; pre-determination of needs - contracting interest - public submission -Public transactions - public service delegations.